Motivation of Activity and Responsibility: SocioPsychologlcal Aspect - Suslavičius, Antanas (Problemos, 1994)
The relation between the causes of man’s social behaviour, decision making, choice of aim and responsibility is discussed. The psychological aspects of responsibility are analysed. The divergent evaluations of responsibility by actor and observer, their differing attributions are discussed as well. The problem of the control of the conditions of act as well as of the possibilities of a subject to influence upon surroundings is considered.